The Impact of Coexistent Hashimoto’s Thyroiditis on Central Compartment Lymph Node Metastasis in Papillary Thyroid Carcinoma - Liu, Yang; Lv, Hongjun; Zhang, Shaoqiang; Shi, Bingyin; Sun, Yushi (Frontiers in Endocrinology, 2021)
Background: Hashimoto thyroiditis (HT) is the most prevalent inflammatory disorder of the thyroid gland. Current studies have reported the coexistence rate between HT and papillary thyroid carcinoma (PTC) is quite high. The objective of this study was to evaluate the impact of HT on the predictive factors of central compartment lymph node metastasis (CLNM) in PTC. Methods: A retrospective investigation was performed on PTC patients. They were subclassified into HT and non-HT groups. The results of preoperative neck ultrasound (US) examinations were reviewed. The clinical characteristics and the predictive value for CLNM were explored and compared between the two groups. Results: A total of 756 patients were included in this study. There were more female patients (86.1%) in the PTC coexistent with the HT group than non-HT group. The patients with HT group had higher preoperative serum level of TSH. There was statistically significant difference between the HT patients and non-HT patients in nodular vascularization. Univariate and multivariate analyses showed that male, age≤45 years old, tumor diameter >1 cm, and presence of suspicious central compartment lymph node on US, irregular nodular shape, multifocal carcinoma were independent predictive factors of CLNM in PTC patients. It was showed that male, age≤45 years old, tumor diameter >1 cm, multifocality, and presence of suspicious central lymph node on US were risk factors for CLNM in non-HT patients. Only tumor diameter >1 cm and presence of suspicious central lymph node on US were independently correlated with CLNM in HT patients. The sensitivity of the multivariate model was 63.5%, and specificity was 88.9% for prediction CLNM in HT patients. For non-HT patients, the AUC was 80.6%, the sensitivity of the multivariate model was 64.5%, and specificity was 85.2%. Conclusions: PTC combined with HT is more common in women, and TSH level in HT group is higher than that in patients with PTC alone. Regardless of that HT is not a related risk factor of CLNM in PTC, our result suggested that different predictive systems should be used for HT and non-HT patients respectively to have a more accurate evaluation of CLNM in clinic.